2006
DOI: 10.1007/s10522-005-6038-x
|View full text |Cite
|
Sign up to set email alerts
|

Organ- and Tissue-specific Alterations in the Anti-apoptotic Protein Bcl-2 in CD1 Female Mice of Different Ages

Abstract: The anti-apoptotic protein Bcl-2, which also has cytoprotective and antioxidant functions might be one of the crucial factors that altogether, establish how a cell may deal with stress and damage, contributing to longevity. Among the controversial issues to understand Bcl-2 functions in vivo, is to establish its content and variation in tissues during an organismal lifespan. In this work we analyzed the changes of Bcl-2 levels in lung, liver, heart, kidney, spleen and brain homogenates obtained from CD1 mice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Findings from the current study show that resistance exercise induced an increase in beclin-1, which was accompanied by decreased Bcl-2 and Bcl-xL protein concentration. It is important to note that several authors have shown that the expression of Bcl-2 and Bcl-xL increases with aging in many tissues [11,42]. Furthermore, the relative Bad/Bcl-2 ratio, a parameter of apoptotic cell death, decreased with the training program.…”
Section: Discussionmentioning
confidence: 98%
“…Findings from the current study show that resistance exercise induced an increase in beclin-1, which was accompanied by decreased Bcl-2 and Bcl-xL protein concentration. It is important to note that several authors have shown that the expression of Bcl-2 and Bcl-xL increases with aging in many tissues [11,42]. Furthermore, the relative Bad/Bcl-2 ratio, a parameter of apoptotic cell death, decreased with the training program.…”
Section: Discussionmentioning
confidence: 98%
“…Small variations in Bcl2 levels can capture tissue specific variations as well as variations during various developmental stages [43]. Bcl2 over-expression (3-fold) resulted in inhibition of Bax activation and slightly delayed release of mitochondrial cytochrome c. Subsequent formation of XIAP-Smac and apoptosome complex were also delayed.…”
Section: Resultsmentioning
confidence: 99%
“…The aged cells were acquired resistance to certain apoptotic molecules such as bcl-2 expression (López-Araiza et al 2006). Bcl-2 gene expression is regulated by c-myb (Weston 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, many authors reported that ageing cells show more resistance and an increased cell survival ratio against oxidative stress (Yeo et al 2000;Suh et al 2002;Lee et al 2008Lee et al , 2009. Aged cells have the capacity to survive environmental stress by altering many types of changeable gene such as bcl-2 and Hsp60 (López-Araiza et al 2006;Lee et al 2008). It was previously reported that aged cells have a higher cell survival capacity to oxidative stress, which involves a blockage of the translocation of Hsp60 followed by SAPK/JNK inactivation, than young cells (Lee et al , 2009.…”
Section: Introductionmentioning
confidence: 99%